Pengaruh Kompensasi, Motivasi, dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan pada PT Kala Prana Consultant - Aprilia Jenianti Muti RIu; Kusuma Chandra Kirana; Syamsul Hadi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Human Resources is the most important asset in a business organization or company, because it is the main body that implements the company's policies and operational activities. Job satisfaction is the response given by employees to their work, both in the form of positive responses and negative responses. Job satisfaction can be achieved by 3 factors, including (i) Compensation, which is in the form of remuneration or work that has been done, (ii) Motivation, namely providing a driving force so that employees are able to work optimally, (iii) Work Discipline, namely employees are able to obey rules that have been made. The purpose of this study is to determine partially and simultaneously the variables of compensation, motivation, and work discipline on employee job satisfaction at PT. Kala Prana Consultant. This study uses a quantitative approach method. The population in this research is 43 employees. Sampling is done by non-probability method and the sampling technique is purposive sampling. The data were analyzed using the IBM SPSS application. The results showed that the compensation variable (X1) had no significant effect on job satisfaction (Y), as evidenced by the results of the t test, namely the t-count value was 1.447 < t table 1.684 and significant 0.156> 0.05. Then the Motivation variable (X2) has a significant effect on Job Satisfaction (Y) as evidenced by the results of the t test, namely the t-count value is 1.753 > t table 1.684 and significant is 0.087 <0.05. And the Work Discipline variable (X3) has a significant effect on job satisfaction (Y), as evidenced by the results of the t-test, namely the t-count value of 3.094 > t-table 1.684 and significant 0.004 <0.05. Keywords: Job Satisfaction, Compensation, Motivation, and Work Discipline.